Upaya Peningkatan Durabilitas Beton Terpapar Klorida dan Sulfat dengan Menggunakan Silica Fume, Semen Tipe II, dan Protective Coating - Sulaeman, Agus; Herdiansah, Yudi; Destianto, Anto (Universitas Kristen Maranatha, 2024)
The durability of concrete material is affected by the environment. Extreme environments that affect the concrete are environments with high chloride and sulfate levels. The most commonly used concrete protection methods are silica fume, type II cement and protective coatings. The tests are carried out included: testing for chloride content, testing on chloride infiltration, visual analysis and testing for changes of length. The specimens was made in 4 variations namely; specimens with type I cement without protection, specimens with type I cement with a protective coating, specimens with type I cement with the addition of silica fume, specimens with type II cement without protection. The specimens were immersed in a solution of chloride and sulfate for 14 days, 28 days, 42 days and 56 days. The results showed that silica fume in type I cement could increase the durability of concrete against chloride but not against sulfates, protective coating could increase the durability of concrete against chloride and sulfates, type II cement could increase the durability of concrete against sulfates but not against metals.